Patient, surgeon, and institutional variation in dual-mobility component use in primary total hip arthroplasty - Benjamin E. Zucker; Joshua T. Howard; Michael R. Whitehouse; Andrew Judge (The Bone & Joint Journal, 2026)
Aims The aim of this study was to quantify the contribution of patient-, surgeon-, and institution-level factors to variation in dual-mobility component use in primary total hip arthroplasty (DM-THA) in England. We sought to determine whether current patterns reflect appropriate patient selection or unwarranted practice variation. We hypothesized that surgeon- and institution-level factors account for a greater proportion of variation in DM-THA use than patient-level characteristics. Methods We analyzed 238,455 primary THAs recorded in the National Joint Registry which were linked with Hospital Episode Statistics for England between 1 January 2018 and 31 December 2022. Using cross-classified multilevel logistic regression modelling, we partitioned variation in DM-THA use attributable to patient, surgeon, and institutional factors. Patient risk factors were included as fixed effects, with random effects specified for surgeons and hospitals to account for clustering. Results Of the total cohort, 7,032 underwent DM-THA. These patients were older, more frail, and more frequently treated for neck of femur fractures. Surgeon-level factors explained 32.4% and institutional factors 22.9% of variation in DM-THA use. Patient-level factors accounted for approximately 10% of the variance (marginal R² = 0.10), while the full model explained 59.8% of variation (conditional R² = 0.598). Findings were consistent in analyses restricted to high-volume surgeons. Conclusion Variation in DM-THA use is predominantly driven by surgeon and institutional practice rather than patient characteristics. Prognostic tools which can identify patients at high dislocation risk, to guide inclusion criteria for targeted randomized trials, are needed to establish evidence-based guidance for DM implant selection and reduce unwarranted practice variation. Cite this article: Bone Joint J 2026;108-B(9):1097–1103.